Models of PaO2 response to the continuous distending pressure maneuver during high frequency oscillatory ventilation in healthy and ARDS lung model pigs - Laviola, Marianna; Rafl, Jakub; Rozanek, Martin; Kudrna, Petr; Roubik, Karel (Experimental lung research, 2016)
UNLABELLED: Purpose/Aim : High-frequency oscillatory ventilation (HFOV) is a method of ventilation that theoretically achieves the goals of lung protective ventilation in acute respiratory distress syndrome (ARDS) patients. It is characterized by a rapid delivery of small tidal volumes at high frequencies oscillating around a continuous distending pressure (CDP). Optimization of CDP is not an easy task and it is titrated empirically in the clinical practice. The aim of this study is to investigate whether the level of CDP consistently affects the shape of the partial pressure of oxygen (PaO2) response to stepwise changes in CDP during HFOV of healthy and ARDS-induced pigs. MATERIALS AND METHODS: We performed two stepwise maneuvers of CDP in 14 pigs: one before and one after the lung lavage, inducing ARDS. For each CDP step performed, we fitted a segment of PaO2 curve with a one-term power model. RESULTS: PaO2 course follows shapes modeled by root, linear, quadratic, and cubic functions for values of PaO2 ≤ 110 mmHg and PaO2 ≤ 200 mmHg, before and after the lung lavage, respectively. PaO2 course follows a shape modeled exclusively by a root function for values of PaO2 > 110 mmHg and PaO2 > 200 mmHg, before and after the lung lavage, respectively. It is not possible to describe a relationship between the shape of the PaO2 course and the values of CDP. CONCLUSIONS: The PaO2 curve may give information about the level of recruitment of alveoli, but cannot be used for optimization of CDP level during HFOV in healthy and ARDS lung model pigs.
Keywords: dechový objem; continuous distending pressure; analýza krevních plynů; Blood Gas Analysis; HFOV; umělé dýchání; ARDS; Female; High-Frequency Ventilation; Pressure; vysokofrekvenční ventilace; kyslík; ženské pohlaví; oxygenation; modely nemocí na zvířatech; Bronchoalveolar Lavage; tlak; Animals; výměna plynů v plicích; prasata; zvířata; Respiration, Artificial; lung lavage; Disease Models, Animal; Respiratory Distress Syndrome; syndrom dechové tísně; Tidal Volume; bronchoalveolární laváž; power model; Oxygen; Swine; Pulmonary Gas Exchange